Optimasi Rute Distribusi Produk Pertalite YangEfektif Dengan Pendekatan Saving Matrix Di Fuel Terminal X - Oktavia Salsa Winanda Pangestu; Ade Christiano; Tri Warcono Adi (SM Institute, 2025)
This study examines the optimization of Pertalite fuel distribution routes at Fuel Terminal X using the Saving Matrix method. The main problem addressed is the inefficiency of current distribution routes, which impacts operational costs, delivery time, and fleet utilization. The objective of this research is to implement the Saving Matrix method to determine more effective distribution routes and to evaluate its effectiveness in terms of cost, travel distance, and delivery time. The study employs secondary data, including the number and locations of gas stations, fuel demand, road classifications, travel distances, and fuel consumption of distribution vehicles. The findings indicate that the Saving Matrix method successfully reduced the total distribution distance from 1,010 km to 580 km, achieving a saving of 430 km (42.6%). Moreover, the total distribution time decreased to 67 hours with a cost of Rp 1,223,552, utilizing eight tank trucks with varying capacities. In conclusion, the application of the Saving Matrix method proved effective in enhancing the efficiency of Pertalite distribution at Fuel Terminal X in terms of cost, time, and fleet usage. Keywords : Optimization, Distribution, Pertalite, Saving Matrix, Vehicle Routing Problem